Alloys-by-design: A low-modulus titanium alloy for additively manufactured biomedical implants. (1st May 2022) - Alabort, E.; Tang, Y.T.; Barba, D.; Reed, R.C.
Graphical abstract: Abstract: The performance of many metal biomedical implants – such as fusion cages for spines – is inherently limited by the mismatch of mechanical properties between the metal and the biological bone tissue it promotes. Here, an alloy design approach is used to isolate titanium alloy compositions for biocompatibility which exhibit a modulus of elasticity lower than the Ti-6Al-4V grade commonly employed for this application. Due to the interest in alloys for personalised medicine, additive manufacturability is also considered: compositions with low cracking susceptibility and with propensity for non-planar growth are identified. An optimal alloy composition is selected for selective laser melting, and its processability and mechanical properties tested. Additive manufacturing is used to engineer an heterogeneous microstructure with outstanding combined strength and ductility. Our results confirm the suitability of novel titanium alloys for lowering the stiffness towards that needed whilst being additively manufacturable and strong.